Pharmacokinetics and Use‐Testing of Apalutamide Prepared in Aqueous Food Vehicles for Alternative Administration. Issue 11 (17th July 2021) - Yu, Alex; Erba, Maura; Hazra, Anasuya
Abstract: Patients may have difficulty swallowing a whole daily dose of 240 mg (4 × 60‐mg tablets) of apalutamide. One of the unique properties of apalutamide tablets is easy disintegration and dispersion when mixed into aqueous vehicles, avoiding the need to crush/split the tablets. To evaluate whether this method of apalutamide tablet administration would be conducive in a patient setting, different variations in preparation were evaluated, and one preparation was tested in humans. In vitro compatibility studies evaluated purity, dose, or stability of different variations of apalutamide in applesauce/yogurt/orange juice/green tea. An open‐label, randomized, crossover phase 1 study in healthy men determined the bioavailability of an apalutamide‐applesauce mixture versus whole tablets based on maximum plasma analyte concentration (Cmax ), area under the plasma analyte concentration‐time curve: AUC0‐72h and AUC0‐168h . Different amounts of applesauce/yogurt/orange juice/green tea as well as durations (up to 6 hours) did not affect the total apalutamide content available. The phase 1 study (n = 12) showed increased total exposure of 5% and peak exposure of 27.6% when comparing the apalutamide‐applesauce mixture with whole‐tablet administration. Variations in preparation times and total content for applesauce/yogurt/orange juice/green tea did not affect the purity, dose, or stability of apalutamide. An apalutamide‐applesauce mixture is a suitable alternative administration method to whole tablets.